ACCESSING SCIENTIFIC INFORMATION - Escobedo Carbonell, Angel; de Armas Rodríguez, Yaxsier; Castello González, Mauro; Choonara, Imti (Revista Cubana de Medicina Tropical, 2017)
Practising evidence based medicine is recognised as essential to ensure that patients receive the best possible treatment. For health professionals to be able to practice evidence based medicine, they need to be able to access scientific information. Unfortunately, many important scientific articles are not freely available. Scientific articles are published in journals owned by large publishers, who for financial reasons, ensure that access is restricted to institutions or individuals that have paid for the right to read the scientific evidence. This article show the limitations of researcher in developing countries to be able to access scientific information.